Creative Teaching in EFL Classrooms: Voices from Afghanistan - Ahmad Fawad Kakar; Kawita Sarwari; Mir Abdullah Miri (Universitas Muhammadiyah Yogyakarta, 2020)
This qualitative research aims to explore the reported experiences of five Afghan EFL instructors at the English Department, Herat University, concerning the creative teaching of English. It specifically investigated the challenges and the opportunities regarding the creative teaching of English that these teachers have encountered in their courses. The researchers employed constructivist perspectives of learning in which learners make meaning out of their previous experiences and knowledge (Hill, 2014) as the theoretical framework to analyze and interpret the data. The data were collected through semi-structured interviews and analyzed by using thematic analysis. The findings indicated that creative teaching made the learning process fun. It also revealed that creative teaching increased students’ participation and motivation because it put students in the center of the learning process. The findings also demonstrated that some students showed resistance toward change—moving from a teacher-centered approach to a student-centered approach—when creative teaching was implemented. It also showed that some instructors needed the support of higher education administrators to incorporate creative teaching into their courses as there was a conspicuous lack of professional development needs in this regard. The study argued that the creative teaching of English positively impacted students’ academic achievements. This study could serve as a significant way to introduce information and strategies on creative teaching to L2 instructors in similar contexts as Afghanistan. The results provided implications for creative teaching in EFL classrooms as well as for the future of teaching English in ESL and EFL contexts.